Da'f al-qayyim al-akhlaqiyah lada ba'd tullab al-Jami'at al-Sa'udiyah : Jami'at al-Ta'if anmudhajan = Moral transgression among university students in Saudi Arabia : a case study at University of Taif / Khalid bin Ali alQarni - alQarni, Khalid Ali (2011)
This study aimed to emphasize the importance of moral values and to identify the causes resulted in the weakness of some ethical values. Moreover, it also aimed to find out the solutions to the phenomenon of moral values weakness based on the sample of this study. The researcher used the descriptive method. The sample of this study was selected randomly, and the number of the respondents were (160) students from the Faculty of Education at Taif University. The researcher developed a questionnaire as a main tool for the survey. Besides, the researcher conducted some interviews with the teaching staffs to take their views regarding the causes of the weakness of some moral values among students as well as their solutions. Through the notice card, the researcher attempted to identify the most important features of the weakness in some moral values among the students of the Faculty of Education. The findings of this study showed a high means of the importance of moral values according to the participants of this study. These values were ordered consecutively as follows (truthfulness, honesty, loyalty, modesty, good company, cleanliness, decency, respect for others, cooperation, and discipline). Regarding the most important causes of the weakness of moral values among students in the Faculty of Education at the University of Taif were as follows (Weakness of religious motive, family disintegration, peer pressure, some books, novels and magazines that contain bad behavior and methods of raising children). According to the views of the participants of this study, the most important methods for solving the weakness of moral values were (family commitment to a role model, the righteous company at the university and in the community – The commitment of university professors to a role model – the use of dialogue and discussion among family members). The study recommended that further Evaluative studies should be carried out on this issue at various educational levels. Moreover, parents should be aware of their responsibility as well as their primary role in the reform of society via creating an atmosphere that is conducive for children at home. Finally, the mosque should play its religious and educational role in encouraging students to behave in the right way.